2015
DOI: 10.1017/jfm.2015.202
|View full text |Cite
|
Sign up to set email alerts
|

An analytical solution to electromagnetically coupled duct flow in MHD

Abstract: The flow of an electrically conducting fluid in an array of square ducts, separated by arbitrary thickness conducting walls, subject to an applied magnetic field is studied. The analytical solution presented here is valid for thick walls and is based on the homogeneous solution obtained by Shercliff (Math. Proc. Camb. Phil. Soc., vol. 49 (01), 1953, pp. 136-144). Arrangements of ducts arise in a number of applications, most notably in fusion blankets, where liquid metal is used both as coolant and for tritium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…At this time, there are a few studies about analytical solution of the MHD flow. Recent work was presented by Bluck and Wolfendale [25] about an analytical solution to the laminar flow of an electrically conducting fluid in an array of partially conducting ducts subjected to an applied magnetic field. These solutions provide an understanding of the physics of such flows and an important benchmarking and validation data for computational MHD.…”
Section: Introductionmentioning
confidence: 99%
“…At this time, there are a few studies about analytical solution of the MHD flow. Recent work was presented by Bluck and Wolfendale [25] about an analytical solution to the laminar flow of an electrically conducting fluid in an array of partially conducting ducts subjected to an applied magnetic field. These solutions provide an understanding of the physics of such flows and an important benchmarking and validation data for computational MHD.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field within the wall satisfies a Laplace equation. The solution to this Hunt-II problem is given in [8]. Note that this solution reduces to the Shercliff solution for wholly insulating walls by setting P n = 0.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Multiplying (28) by U, integrating over the cross-section and using (19) and the results in [8] and [10], it can be shown that…”
Section: H 1 Heat Transfer Casementioning
confidence: 99%
See 1 more Smart Citation
“…An electrically conducting fluid flow in an array of square ducts, separated by conducting walls of arbitrary thickness, subject to an applied magnetic field has been investigated [14]. An investigation of unsteady hydromagnetic natural convection heat and mass transfer flow past an impulsively moving infinite vertical plate embedded in a uniform porous medium when the temperature of the plate has a temporarily ramped profile has been carried out [15].…”
Section: Introductionmentioning
confidence: 99%